Neuromuscular Stability of Dental Occlusion in Patients Treated with Aligners and Fixed Orthodontic Appliance: A Preliminary Electromyographical Longitudinal Case-Control Study - Claudia Paola Bruna Dellavia; Giacomo Begnoni; Cristiana Zerosi; Guia Guenza; Natalie Khomchyna; Riccardo Rosati; Federica Musto; Gaia Pellegrini (Diagnostics, 2022)
The aim of the present study was to evaluate if, after treatment with aligners (ALIGN) and fixed orthodontic appliance (FOA), alterations of the neuromuscular activity may occur and if differences in these changes can be detected between the two treatments. Sixteen healthy patients (7 FOA, 9 ALIGN) with class I or class II molar relation were recruited. Standardized surface electromyography (ssEMG) was used to evaluate the activity of the masticatory muscles (masseters-MM and temporalis-TM) before the beginning of the orthodontic treatment (T1), at the end (T2), and 3 months (T3) after the end of the treatment. Intragroup (within timepoints) and intergroup differences were statistically analyzed. At T1, the mean values of each ssEMG index were within the normal range in both groups. At T2, the FOA group showed larger differential recruitment of the MM than TA muscles with a value slightly over the normal range. All the indexes were normalized at T3, and no differences emerged between groups. In the FOA group, the index of MM symmetrical contraction increased significantly at T3 compared to T1 and T2. In the ALIGN group, no significant changes were observed between each timepoint. In FOA subjects, a slight alteration of the muscular activity appeared immediately after bracket removal and this alteration normalized after 3 months of rescue. In subjects treated with aligners, no significant alteration of the muscular activity was assessed.